Harmonisasi Hukum Acara Perdata dan Hukum Acara Peradilan Tata Usaha Negara dalam Penyelesaian Sengketa Dualisme - Amanda Jihan Namira; Sidi Ahyar Wiraguna (AHKAM, 2025)
Disputes containing both civil law and administrative law elements often generate a dualism of judicial jurisdiction due to the lack of clear boundaries between the general courts and the Administrative Court (PTUN), a situation exacerbated by normative inconsistencies, overlapping regulations, and divergent judicial interpretations, so that a single object of dispute may be examined under two legal regimes simultaneously and thereby create legal uncertainty. This study aimed to analyze the points of intersection between civil procedural law and PTUN procedural law, identify obstacles arising in mixed-element disputes, and formulate theoretical solutions for harmonizing jurisdiction. The research employed a normative juridical method with statutory, conceptual, and case approaches through the analysis of primary, secondary, and tertiary legal sources. The findings show that jurisdictional dualism primarily occurs in disputes over government contracts, procurement of goods and services, and revocation of business licenses, which simultaneously contain private and administrative aspects, while the lack of synchronization in evidentiary mechanisms and the differing orientations of dispute resolution between the general courts and PTUN reinforce the potential for dual forums. The study concludes that harmonization is required through the strengthening of rules on subject-matter jurisdiction, the application of limited forum prorogatum, the establishment of an integrated court model, and the consistent development of jurisprudence. The implications of this research affirm that the alignment of procedural laws is a crucial prerequisite for ensuring legal certainty, enhancing the efficiency of dispute resolution, and strengthening public trust in the judicial system.